The production function and profitability analysis of Gracilaria sp. seaweed polyculture with milkfish (Chanos chanos) and black tiger shrimp (Penaeus monodon) - Iis Diatin; Irzal Effendi; Meri Alvina Taufik (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Diatin I, Effendi I, Taufik MA. 2020. The production function and profitability analysis of Gracilaria sp. seaweed polyculture with milkfish (Chanos chanos) and black tiger shrimp (Penaeus monodon). Biodiversitas 21: 4747-4754. Gracilaria seaweed is the main ingredient for making agar as a source of food and industry. Gracilaria culture in ponds with a polyculture system is one of the potential seaweed cultivation in Indonesia. This study was aimed to analyze the productivity, production input optimation, and profitability on the polyculture system of Gracilaria sp. with milkfish (Chanos chanos) and black tiger shrimp (Penaeus monodon). The survey method was used to notify the seaweed farmers from Indramayu, West Java, Indonesia. The study data were obtained from all seaweed polyculture farmers populations in the observational location by census containing two farmers groups, namely Gracilaria sp. with milkfish and black tiger shrimp (GMS symbol) and Gracilaria sp. with milkfish (GM symbol) polyculture system. This study resulted that GMS polyculture system obtained higher productivity than GM polyculture system. The GMS business scale was in the increasing return to scale condition, while GM was in the decreasing return to scale condition. The optimal condition of GMS polyculture system was performed by improving the black tiger shrimp seed input, milkfish seed, and milkfish feed, besides declining the working hours, while GM polyculture system was performed by decreasing the milkfish feed and farmers working hours. When the optimal condition is applied to the GMS polyculture system, then the business profit reaches five times, resulting in an increased profit margin of 112% with R/C becomes 134%. Meanwhile, GM polyculture system only reaches 65% business profit, 65% profit margin, and 25% R/C. The investment payback period from both polyculture systems became shorter. The application of production input efficiency on the GMS polyculture system is more prospective than GM polyculture system.